Structural adaptations of cell walls of Chlorella vulgaris Beij. (Chlorophyta) the action of ions zinc and lead - Grubinko, V.V.; Kostiuk, K.V.; Lutsiv, A.I. (Альгология, 2014)
Main specific and nonspecific cells responses and membrane structures participation in formation of cells resistance of Chlorella vulgaris in stress conditions, caused by heavy metals (zinc, lead) in toxic concentrations are analyzed. The cell membranes participation in adaptation to toxicants (formation of growths, multiplication membranes, fluidization, forming of aquaporin, apoptosis), which are first exposed to stressors, is discussed. Found specific and nonspecific reactions in membrane formation are proposed to use as biomarkers of toxicity.